Taman Kota Punti Kayu sebagai Ruang Hijau Kota : Edukasi Manfaat bagi Kesehatan Fisik dan Mental Bagi Masyarakat Kota Palembang - Sinta Bella Agustina; M Bambang Purwanto (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Punti Kayu City Park in Palembang has a strategic role as the lungs of the city and an ecotourism-based economic center for the surrounding community. However, challenges such as suboptimal environmental management, low public awareness of park conservation, and economic utilization that has not been maximized are still obstacles. This community service activity aims to improve the sustainability of the park through environmental education, empowerment of local MSMEs, and revitalization of park facilities. The methods used include initial observation, coordination with related parties, workshops and seminars, creative economy training, and 3R-based reforestation and waste management programs (Reduce, Reuse, Recycle). The results of the activity showed an increase in public awareness of the importance of city parks, increasing the skills of MSME actors in digital marketing, and improving park infrastructure to support educational tourism. The implication of this program is the formation of a sustainable park management model based on community participation, which can be used as an example for other green areas. It is hoped that this program will continue through long-term mentoring and cross-sector collaboration so that the benefits are wider.